The study on the barriers of franchises to enter into global market / Khiruddin Rosli - Rosli, Khiruddin (Faculty of Business and Management, 2011)
Barrier of entry is a circumstance particular to a given industry that creates disadvantages for new competitors attempting to enter the market. These may include government regulations, economic sectors and market conditions. In recent years several competition scholars have concluded that the debate about entry barriers should be considered irrelevant to competition policy. The research study “A Study on Barriers of Franchises to Enter into Global Market” had been conducted to obtain the results at several selected franchises from a different industry from Johor. This research has been answered by 70 respondents through questionnaire. Instead of it, the statistical Package for the Social Science (SPSS) version 16.0 has been used to summarize the data. Based on this research the result indicates that increase in cost is the most barriers faced by those franchises. Besides that results show, there are significant relationship between the independent variables which include Control of Headquarter, Complex Corporate Governance and Cultural Differences. As a conclusion, the results of the findings that include the analysis of the demographic profile, general information on barriers to entry of franchises to enter into global market. For the recommendation of this study made based on several logical factors and impact of current situation on the global market places.